Study of the oxidative stability via Oxitest and Rancimat of phenolic-rich olive oils obtained by a sequential process of dehydration, expeller and supercritical CO2 extractions - Chabni, Assamae; Bañares, Celia; Torres, Carlos F. (Frontiers in Nutrition, 2024)
The oxidative stability of olive oils extracted by different methods, i.e. conventional 2-phase extraction (cOO), and sequential extraction by expeller press (eOO) and supercritical CO2 (SCOO), was determined by using two accelerated oxidation methods, Oxitest and Rancimat, in the temperature range 90-160°C. A good correlation between the two techniques was obtained (r 2 =0.996). Oxitest showed, however, shorter induction times and less sample quantity (1g vs. 3g in Rancimat) requirements, suggesting that it could be a good and faster alternative to Rancimat for the evaluation of the oil oxidative stability. The kinetic analyses carried out provided Arrhenius activation energies, enthalpies, entropies and Gibb's free energies of activation, temperature coefficients, Q10 factors, and the oxidative stability indexes at 20°C (OSI20) for the different oils. cOO showed OSI20 values of 38.5 and 42.5 months, by the Rancimat and Oxitest methods, respectively. Furtheromore, eOO and SCOO showed OSI20 values of 43.3 and 138.6 months by Rancimat and 67 and 142 months by the Oxitest method, respectively. The strong correlation found between the phenolic content of the oils and their OSI20 values confirms that a higher oil phenolic content would improve the oxidative stability of the oils.